Chapter Transfer of Non-Academic Skills in Academic Context: towards a Sustainable Employability - Sabatano, Fausta (Studies on Adult Learning and Education, 2018)
This essay is an element of dialogue between educational practices acquired in territorial education contexts and the University. In particular, starting from the 10-year long experience consolidated in three educational centres operating in border areas of the Province of Naples, a series of 'key competences' have been highlighted that are indispensable to the containment of social risk disadvantage in an inclusion (Bertolini 1977; Freire 2004; Rossi 2014; Sabatano 2015a, 2015b) and well-being project (Iavarone 2007, 2009) from an educational point of view. Such competencies have become subject of a 'participatory didactic planning' between expert educators working in these contexts and a university course on 'Pedagogy of relationships' within the Department of Motor Science and Well-Being at the University of Naples Parthenope. The participatory planning practice has set the most ambitious goal of achieving a 'system methodology' to be used in the curriculum-design of the university courses in order to make the academic education offer a proper link element between the educational demand of young people, the demand for professional skills in the territory and the emerging social needs in order to improve employability processes. The main results that this experience has highlighted can be deducted from the student's satisfaction survey, as well as from the data collected and processed by the University Assessment Team, in the Department's Joint Commission Reports, which show a clear and overall improvement of the communication processes between non-academic institutions collaborating with the University for the conduct of internships, training sessions and placement-targeted activities. The empirical evidence and the positive results obtained provide substantial comfort in considering that the experience gained can be a 'good practice' to be included in the didactic planning process of the courses, even in relation to the need to improve the educational and didactic offer with reference to the new quality assurance parameters (QA) for the periodic accreditation of the CdS according to the AVA-ANVUR legislation in force